Igloo: soundly linking compositional refinement and separation logic for distributed system verification - Sprenger, Christoph; Klenze, Tobias; Eilers, Marco; Wolf, Felix A.; Müller, Peter; Clochard, Martin; Basin, David (Proceedings of ACM on programming languages, 2020)
Lighthouse projects like CompCert, seL4, IronFleet, and DeepSpec have demonstrated that full system verification is feasible by establishing a refinement between an abstract system specification and an executable implementation. Existing approaches however impose severe restrictions on the abstract system specifications due to their limited expressiveness or versatility, or on the executable code due to their use of suboptimal code extraction or inexpressive program logics. We propose a novel methodology that combines the compositional refinement of event-based models of distributed systems with the verification of full-fledged program code using expressive separation logics, which support features of realistic programming languages like heap data structures and concurrency. Our main technical contribution is a formal framework that soundly relates event-based system models to program specifications in separation logics. This enables protocol development tools to soundly interoperate with program verifiers to establish a refinement between the model and the code. We formalized our framework, Igloo, in Isabelle/HOL. We report on three case studies, a leader election protocol, a replication protocol, and a security protocol, for which we refine formal requirements into program specifications that we implement in Java and Python and prove correct using the VeriFast and Nagini tools.